Deconstructing “The Bridge on the Drina” in the Context of Postcolonial Criticism - Abdula, Sevba (The Balkans Politics, History and Society)
Postcolonialism is a theory and critical approach that deals with the postcolonial period and generally developed as an anti-colonial reaction. This theory analyses the literary and cultural structures formed during and after the colonial period, especially in the countries that were former colonies of Europe. Therefore, the origins of postcolonialism can be traced back to the historical resistance against colonial occupation and imperialist control (Young, 2001: 60). The success of the resistance paved the way for a fundamental challenge to the political and con-ceptual structures of the systems on which such domination is based. In histori-cal terms postcolonial theory problematises the legacy of colonialism, its effects on societies, and how these effects are dealt with. However, the prefix ‘post-’ in the term should be considered not only in a temporal sense, but also as a sign of a conceptual movement that goes beyond existing theoretical understandings of the world.